Heart Rate Response and Flexibility Following Single Bout of Training Using a Seated Elliptical Trainer Among Younger and Older Adults. (May 2023) - Topp, Robert; Etnoyer-Slaski, Jena; Greenstein, Jay
The purpose of this study was to compare the effect of a 30-minute activity session using a seated elliptical trainer on heart rate response, knee and ankle range of motion and satisfaction among older and younger adults. Prior to and following completing a 30-minute bout of activity using a seated elliptical trainer, each participant's leg flexibility was assessed. During every minute of the activity, the participant's heart rate was recorded. Following the activity, the participants reported their satisfaction with the trainer. Older participants exhibited a greater heart rate response relative to their estimated maximum heart rate during and reported greater satisfaction with the elliptical trainer compared with younger participants. Both groups increased their leg flexibility following use of the trainer. Nurses could prescribe 30 minutes of activity using a seated elliptical trainer to employees in sedentary occupations to improve cardiovascular health and leg flexibility particularly among older adults.